(untitled) (Jurnal EurekaMatika, 2020)
A matrix algebra over a field cannot necessarily be decomposed into a direct sum of its submodules to become fine graded over a group G. This decomposition into a fine graded algebra is determined by the group used. In the case of the matrix algebra, if a cyclic group is used as an index to decompose the matrix algebra into a fine graded algebra, it results in submodules that are not linearly independent, and thus not a direct sum. Conversely, when using a non-cyclic group, the submodules can form a direct sum and satisfy the conditions such that a fine grading for the matrix algebra can be performed. The support of a matrix algebra will form a subgroup, and every non-zero element in possesses an inverse. Keywords: Direct sum, Fine graded, Graded algebra, Matrix algebra. ABSTRAK Suatu aljabar matriks atas lapangan belum tentu dapat di dekomposisi menjadi hasil jumlah langsung dari submodulnya sehingga menjadi fine graded atas suatu grup G. Dekomposisi menjadi fine graded ini ditentukan oleh grup yang digunakan. Pada kasus aljabar matriks bila digunakan grup siklik sebagai indeks dalam mendekomposisi suatu aljabar matriks menjadi aljabar yang fine graded mengakibatkan submodulnya menjadi tidak bebas linear, sehingga bukan suatu jumlah langsung. Sedangkan ketika menggunakan grup non-siklik, submodulnya bisa merupakan jumlah langsung dan memenuhi sehingga fine grading untuk aljabar matriks dapat dilakukan. Support dari suatu alajabar matriks akan membentuk subgrup dan setiap elemen tak nol di mempunyai invers.